Pengaruh Mekanisme Corporate Governance, Profitabilitas, Intellectual Capital, dan Corporate Risk Disclosure Terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur Yang Terdaftar di Indeks Saham Syariah Indonesia Tahun 2014-2016) - Ulil Albab; Fitri Laela Wijayati (EBBANK, 2018)
This study aims to determine the effect of economic value added,intellectual capital, and corporate governance on firm value. The object studied in this research is manufacturing companies listed in Indonesia Sharia Stock Index for the period 2014-2016. The sample was chosen by using purposive sampling technique and obtained by 30 companies. This study uses secondary data obtained from annual reports of sample companies obtained through the Indonesia Stock Exchange website (www.idx.co.id). The results show that economic value added negative effect on the firm value, intellectual capital positive effect on the firm value, have an effect on firm value while managerial ownership, board of commissioners, and audit committee have no effect on firm valuerelationship with CEI and ISR. CEI and ISR has relationship with sharia bank performance